The sensitivity of primary productivity in Disko Bay, a coastal Arctic ecosystem, to changes in freshwater discharge and sea ice cover - Eva Friis Møller; Asbjørn Christensen; Janus Larsen; Kenneth D. Mankoff; Mads Hvid Ribergaard; Mikael Sejr; Philip Wallhead; Marie Maar (Ocean Science, 2023)
The Greenland ice sheet is melting, and the rate of ice loss has increased 6-fold since the 1980s. At the same time, the Arctic sea ice extent is decreasing. Meltwater runoff and sea ice reduction both influence light and nutrient availability in the coastal ocean, with implications for the timing, distribution, and magnitude of phytoplankton production. However, the integrated effect of both glacial and sea ice melt is highly variable in time and space, making it challenging to quantify. In this study, we evaluate the relative importance of these processes for the primary productivity of Disko Bay, west Greenland, one of the most important areas for biodiversity and fisheries around Greenland. We use a high-resolution 3D coupled hydrodynamic–biogeochemical model for 2004–2018 validated against in situ observations and remote sensing products. The model-estimated net primary production (NPP) varied between 90–147 gC m−2 yr−1 during 2004–2018, a period with variable freshwater discharges and sea ice cover. NPP correlated negatively with sea ice cover and positively with freshwater discharge. Freshwater discharge had a strong local effect within ∼ 25 km of the source-sustaining productive hot spots during summer. When considering the annual NPP at bay scale, sea ice cover was the most important controlling factor. In scenarios with no sea ice in spring, the model predicted a ∼ 30 % increase in annual production compared to a situation with high sea ice cover. Our study indicates that decreasing ice cover and more freshwater discharge can work synergistically and will likely increase primary productivity of the coastal ocean around Greenland.

Greenlandic sea ice products with a focus on an updated operational forecast system - Leandro Ponsoni; Mads Hvid Ribergaard; Pia Nielsen-Englyst; Tore Wulf; Jørgen Buus-Hinkler; Matilde Brandt Kreiner; Till Andreas Soya Rasmussen (Frontiers in Marine Science, 2023)
Sea ice information has traditionally been associated with Manual Ice Charts, however the demand for accurate forecasts is increasing. This study presents an improved operational forecast system for the Arctic sea ice focusing on the Greenlandic waters. In addition, we present different observational sea ice products and conduct inter-comparisons. First, a re-analysis forced by ERA5 from 2000 to 2021 is evaluated to ensure that the forecast system is stable over time and to provide statistics for the users. The output is similar to the initial conditions for a forecast. Secondly, the sea ice forecast system is tested and evaluated based on two re-forecasts forced by the high resolution ECMWF-HRES forecast for the period from January 2019 to September 2021. Both the re-analysis and the re-forecasts include assimilation of sea surface temperatures and sea ice concentrations. We validate the re-analysis and the re-forecast systems for sea ice concentration against different remotely sensed observational products by computing the Integrated Ice Edge Error metric at the initial conditions of each system. The results reveal that the re-analysis and the re-forecast perform well. However, the summertime retreat of sea ice near the western Greenlandic coast seems to be delayed a few days compared with the observations. Importantly, part of the bias associated with the model representation of the sea ice edge is associated with the observational errors due to limitations in the passive microwave product in summertime and also near the coast. An inter-comparison of the observational sea ice products suggests that the model performance could be improved by assimilation of sea ice concentrations derived from a newly-developed automated sea ice product. In addition, analysis of persistence shows that the re-forecast has better skill than the persistence forecast for the vast majority of the time.

Should Sea-Ice Modeling Tools Designed for Climate Research Be Used for Short-Term Forecasting? - Elizabeth Hunke; Richard Allard; Philippe Blain; Ed Blockley; Daniel Feltham; Thierry Fichefet; Gilles Garric; Robert Grumbine; Jean-François Lemieux; Till Rasmussen; Mads Ribergaard; Andrew Roberts; et al. (Current Climate Change Reports, 2020)
In theory, the same sea-ice models could be used for both research and operations, but in practice, differences in scientific and software requirements and computational and human resources complicate the matter. Although sea-ice modeling tools developed for climate studies and other research applications produce output of interest to operational forecast users, such as ice motion, convergence, and internal ice pressure, the relevant spatial and temporal scales may not be sufficiently resolved. For instance, sea-ice research codes are typically run with horizontal resolution of more than 3 km, while mariners need information on scales less than 300 m. Certain sea-ice processes and coupled feedbacks that are critical to simulating the Earth system may not be relevant on these scales; and therefore, the most important model upgrades for improving sea-ice predictions might be made in the atmosphere and ocean components of coupled models or in their coupling mechanisms, rather than in the sea-ice model itself. This paper discusses some of the challenges in applying sea-ice modeling tools developed for research purposes for operational forecasting on short time scales, and highlights promising new directions in sea-ice modeling.

Greenland coastal air temperatures linked to Baffin Bay and Greenland Sea ice conditions during autumn through regional blocking patterns - Thomas J. Ballinger; Edward Hanna; Richard J. Hall; Jeffrey Miller; Mads H. Ribergaard; Jacob L. Høyer (Climate Dynamics, 2018)

Atmospheric and oceanic climate forcing of the exceptional Greenland ice sheet surface melt in summer 2012 - Edward Hanna; Xavier Fettweis; Sebastian H. Mernild; John Cappelen; Mads H. Ribergaard; Christopher A. Shuman; Konrad Steffen; Len Wood; Thomas L. Mote (International Journal of Climatology, 2014)
The NASA announcement of record surface melting of the Greenland ice sheet in July 2012 led us to examine the atmospheric and oceanic climatic anomalies that are likely to have contributed to these exceptional conditions and also to ask the question of how unusual these anomalies were compared to available records. Our analysis allows us to assess the relative contributions of these two key influences to both the extreme melt event and ongoing climate change. In 2012, as in recent warm summers since 2007, a blocking high pressure feature, associated with negative NAO conditions, was present in the mid‐troposphere over Greenland for much of the summer. This circulation pattern advected relatively warm southerly winds over the western flank of the ice sheet, forming a ‘heat dome’ over Greenland that led to the widespread surface melting. Both sea‐surface temperature and sea‐ice cover anomalies seem to have played a minimal role in this record melt, relative to atmospheric circulation. Two representative coastal climatological station averages and several individual stations in south, west and north‐west Greenland set new surface air temperature records for May, June, July and the whole ( JJA ) summer. The unusually warm summer 2012 conditions extended to the top of the ice sheet at Summit, where our reanalysed (1994–2012) DMI Summit weather station summer ( JJA ) temperature series set new record high mean and extreme temperatures in 2012; 3‐hourly instantaneous 2‐m temperatures reached an exceptional value of 2.2°C at Summit on 11 July 2012. These conditions translated into the record observed ice‐sheet wide melt during summer 2012. However, 2012 seems not to be climatically representative of future ‘average’ summers projected this century.